(untitled) (Global Journal of Science Frontier Research, 2014)
A field experiment was conducted during the 2012 and 2013 rainy season at the Kwara State University Teaching and Research Farm located in Malete. The aim was to determine the effect of different weed control methods on Weed infestation, growth and yield of soybeans (variety TGX 1448 -2E). The experiment consisted of 8 treatments, namely, the application of metolachor at 1.5, 2.0 nd 2.5 kg a.i./ ha, pendimethalin at 1.5, 2.0 and 2.5 kg a.i./ha, a tank mixture of metolachlor + diuron at 1.5 + 0.5, 2.0 + 1.0 and 2.5 + 1.5 kg a.i./ha, pendimethalin + diuron at 1.5 + 0.5, 2.0 + 1.0 and 2.5 + 1.5 kg a.i./ha, metolachor at 2.0 kg a.i. /ha plus I supplementary hoe weeding (SHW) at 6 WAS, pendimethalin at 2.0 kg a.i. /ha plus supplimentary hoe weeding (SHW) at 6WAS, metolachlor + diuron at 1.0 +0.5 kg a.i. /ha plus ISHW, pendimethalin + diuron at 1.5 +0.5 plus ISHW at 6WAS, weeding at 3 and 6 WAS and a weedy check. Results show that all the herbicide treatments significantly reduced weed infestation compared with the weedy check. However, metolachlor + diuron integrated with ISHW was more effective than the application of only herbicides in the control of weeds throughout the crop life. This weed control method also resulted in significantly better growth and higher yield. Therefore for better growth and higher yields, metolachlor + diuron integrated with ISHW at 6 WAS is recommend to formers in the Southern Guinea Savanna of Nigeria.